Quality of bread rolls fortified with date fruit pomace: Structure, proximate composition, staling, and sensory evaluation - Alaa Almoumen; Huda Mohamed; Bhawna Sobti; Mutamed Ayyash; Rabih Kamleh; Ali H. Al-Marzouqi; Afaf Kamal-Eldin (NFS Journal)
This study explored the effect of fortification of bread rolls by a high-fibre dietary ingredient from date fruit pomace. Structure, proximate composition, texture, staling, and sensory quality of bread rolls were studied. Flour fortification with sugar-free pomace (0, 5, 10, 15, and 20 %, w/w) led to bread having darker crust and crumbs in a concentration-dependent manner (P < 0.05). Increasing the pomace concentration levels also led to dense crumb structure, especially at the 20 % level. The proximate composition (on dry basis %) ranged as follows: protein (15.4–16.6 %), ash (2.1–2.7 %), fat (1.8–2.8 %), carbohydrates (73.6–57.5 %), and total dietary fibre (5.7–22.4 %). At 20 % fortification, bread moisture and weight increased by 12 % and 10 %, diameter and specific volume decreased by 16 % and 54 %, hardness, springiness, and chewiness increased by 57 %, 28 % and 62 %, and cohesiveness decreased by 18 % compared to the control, respectively (P < 0.05). The differences in the texture and physical parameters of the different bread rolls were significant during four days of storage with all bread rolls becoming smaller and denser. As fibre concentration increased, the bread became heavier with noticeable textural changes such as increased hardness and chewiness. Despite these changes, the rolls were acceptable in a consumer test, especially at moderate fibre levels. Therefore, the date fruit high fibre dietary ingredient holds promise for incorporation into bread-making processes to enhance daily fibre intake.